Aplikasi Dosis Vermikompos dan Urea Pada Tanaman Kedelai Varietas Anjasmoro di Tanah Berpasir - Hesti Pujiwati; Widodo Widodo; Wuri Prameswari; Umi Salamah; Leonardo Dharmawangsa; Edi Susilo; Muhimmatul Husna (Institut Pertanian Bogor, 2021)
The low area for soybean plantation is still a major problem in meeting soybean needs. One of the efforts to increase national soybean production is by expanding the planting area by utilizing the sandy soil area that is still not used for soybean cultivation. This research was conducted from September-November 2020 in a greenhouse of the Agronomy Laboratory, Bengkulu University. This study aims to obtain the best dose of urea and vermicompost for the growth and yield of soybean in sandy soil. The research design used a completely randomized block design with two factors and 3 replications. The first factor was the dose of urea consisting of four levels, namely U0 = 0 kg ha-1, U1 = 50 kg ha-1, U2 = 100 kg ha-1, and U3 = 150 kg ha-1. The second factor was the dose of vermicompost, namely K0 = 0 ton ha-1, K1 = 5 tons ha-1, K2 = 10 ton ha-1, and K3 = 15 ton ha-1. The measured variables were the plant growth and the yield. Soil and vermicompost analyses were carried out before the study. The results showed that there was an interaction between the vermicompost and the urea dosages. The 100 kg ha-1 urea and the 10 ton ha-1 vermicompost treatment gave the highest plant height. The 150 kg ha-1 urea dan the 15 ton ha-1 vermicompost treatment formed the most number of branches. The highest soybean yield was given by 15 ton ha-1 vermicompost and 50 kg ha-1 urea to the total pod and the seed weight. Keywords: sandy soil, soybean, urea, vermicompost